Lebendiger Umgang mit den Toten - der moderne Familienroman in Europa und Übersee - Hillmann, Heinz; Hühn, Peter (Europäische Schneisen, 2012)
Since the nineties of the last century there his an increase of family novels in Germany. Theese novels represent a new model series of so-called 'father novels' that preceded them. The new 'generational novels' take up the exploratory gesture of the father novels. The contributions collected in this volume address the topic and dedicate themselves to exemplary novels from Europe and overseas.